(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This paper examines the development of financial technology (Fintech) in Uzbekistan and South Korea, focusing on South Korea’s digital sandbox initiative as a model for fostering Fintech innovation. By comparing regulatory environments, market conditions, and government support, this study aims to identify key takeaways for Uzbekistan’s Fintech ecosystem. The study highlights how Uzbekistan can adopt and adapt sandboxing approaches to accelerate its Fintech growth.